Gambaran Pemakaian Antibiotika Setelah Implementasi Pedoman Pemakaian Antibiotika di Bangsal Kenanga RSUD Arifin Achmad Provinsi Riau Periode Juni-Agustus 2016 - Dani Rosdiana; Mukhyarjon Mukhyarjon; Dewi Anggraini (Fakultas Kedokteran Universitas Riau, 2017)
Implementation of antibiotic guideline as part of “Antibiotic Stewardship Programs (ASPs)”, can both optimize thetreatment of infections and reduce adverse events associated with antibiotic use, antibiotic resistance and savinghospitals funds. This study describes quantitative and qualitative evaluation and cost of antibiotic use afterimplementation of antibiotic guideline in Kenanga ward Arifin Achmad General Hospital.This research was a descriptiveprospective study. All inpatients given antibiotic in Kenanga ward from June – August 2016 were evaluated. Thequantitative antibiotic use was calculated with DDD (daily define dose) meanwhile Gyssens method was used tocalculate qualitative of antibiotic use. There were 137 patients fulfilled inclusion criteria. The most antibiotic usedwere ceftriaxone, ciprofloxacin, levofloxacin, meropenem and cefoperazone. There was increased consumption ofquinolone class antibiotics. The highest DDD’s antibiotic was ceftriaxone (96.5). Qualitative measurement showedthat rational antibiotic (Gyssens category 0) was 46%, irrational (Gyssens category I - IV) was 35 % and no indicationof antibiotic use (Gyssens category V) was 19%. The total cost of antibiotics in this period were Rp 41,444,766.Afterantibiotic guideline implementation, we found that the most frequent antibiotic was ceftriaxone and irrational use ofantibiotic was still high.